Phenomenology and Hermeneutics: challenging education? - Conte, Elaine (2019)
This paper develops the challenge that the creative imagination points out to thereductionism position of the mere association of technology in the core of education. We analyze the works of Ricoeur, Gadamer, and Habermas on phenomenology andhermeneutics to surpass the descriptive position and the self-statements of thePedagogy discourses. The hermeneutics asks for a comprehensive position to link the traditional knowledge about e education and the complexity of the new paradigms that state the introduction of the virtual resources on education.